Understanding the Social Networks That Form within the Context of an Obesity Prevention Intervention - Sabina B. Gesell; Kimberly D. Bess; Shari L. Barkin (Hindawi Limited, 2012)
Background. Antiobesity interventions have generally failed. Research now suggests that interventions must be informed by an understanding of the social environment. Objective. To examine if new social networks form between families participating in a group-level pediatric obesity prevention trial. Methods. Latino parent-preschool child dyads (N=79) completed the 3-month trial. The intervention met weekly in consistent groups to practice healthy lifestyles. The control met monthly in inconsistent groups to learn about school readiness. UCINET and SIENA were used to examine network dynamics. Results. Children's mean age was 4.2 years (SD=0.9), and 44% were overweight/obese (BMI≥85th percentile). Parents were predominantly mothers (97%), with a mean age of 31.4 years (SD=5.4), and 81% were overweight/obese (BMI≥25). Over the study, a new social network evolved among participating families. Parents selectively formed friendship ties based on child BMI z-score, (t=2.08; P<.05). This reveals the tendency for mothers to form new friendships with mothers whose children have similar body types. Discussion. Participating in a group-level intervention resulted in new social network formation. New ties were greatest with mothers who had children of similar body types. This finding might contribute to the known inability of parents to recognize child overweight.